PERLINDUNGAN HUKUM TERHADAP PENUMPANG MASKAPAI LION AIR YANG MENGALAMI KETERLAMBATAN PENERBANGAN DI BANDARA INTERNASIONAL MINANGKABAU - Dwikornida, Zaini Ahmad dan (Normative Jurnal Ilmiah Hukum, 2021)
From the results of research conducted on the airline's legal protection for Lion Air airline passengers who experienced flight delays, it was found that the Minister of Transportation Regulation Number 89, 2015 had not been implemented properly for Lion Air airlines, so that many passengers were harmed by frequent flight delays, and obstacles in providing legal protection to passengers, namely financial, planning, in terms of organizing, in terms of direction, in terms of supervision, limited human resources, so that the obstacles faced can be solved properly, namely providing spare aircraft, improving management, carrying out the Regulation of the Minister of Transportation Number 89, 2015 properly and the provision of a Lion Air cash office at the Minangkabau International Airport.